2009
DOI: 10.1158/0008-5472.can-09-1591
|View full text |Cite
|
Sign up to set email alerts
|

β1-Integrin Circumvents the Antiproliferative Effects of Trastuzumab in Human Epidermal Growth Factor Receptor-2–Positive Breast Cancer

Abstract: Resistance to trastuzumab, the monoclonal antibody targeting human epidermal growth factor receptor 2 (HER-2), is a major concern for HER-2-positive metastatic breast cancer (MBC) patients. To date, HER-2 status is the only available biomarker for selecting patients for trastuzumab-based therapy. β 1 -Integrin, an adhesion molecule involved in cell survival and drug resistance, shares common downstream signaling elements with HER-2, such as the phosphatidylinositol 3-kinase/Akt and extracellular signal-regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 42 publications
1
65
0
Order By: Relevance
“…For example, HER2 function and resistance to HER2-targeted therapies were previously associated with integrin-mediated adhesion to the extracellular protein laminin-5 in association with increased FAK signaling . Overexpression of b 1 integrin has also been shown to mediate trastuzumab resistance (Lesniak et al, 2009). Furthermore, the erbB growth factor heregulin has been shown to regulate a v b 3 integrin levels in invasive breast cancers to affect downstream MAPK signaling (Vellon et al, 2005).…”
Section: Igf-1r-mediated Invasion In Her2-positive Cancer Cellsmentioning
confidence: 99%
“…For example, HER2 function and resistance to HER2-targeted therapies were previously associated with integrin-mediated adhesion to the extracellular protein laminin-5 in association with increased FAK signaling . Overexpression of b 1 integrin has also been shown to mediate trastuzumab resistance (Lesniak et al, 2009). Furthermore, the erbB growth factor heregulin has been shown to regulate a v b 3 integrin levels in invasive breast cancers to affect downstream MAPK signaling (Vellon et al, 2005).…”
Section: Igf-1r-mediated Invasion In Her2-positive Cancer Cellsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Moreover, the overall response rate of women diagnosed with HER2-positive metastatic breast cancer and treated with trastuzumab as a single first-line agent is only 26%; that is, > 70% of HER2-overexpressing metastatic breast carcinomas show a resistance to trastuzumab ab initio. A variety of possible mechanisms of escape from trastuzumab appear to involve many of the same biomarkers that have been implicated in the biology of CS-like cells: e.g., the overexpression of the stem cell-related marker CD44, leading to a loss or blockage of the trastuzumab-binding site at the extracellular domain of HER2; 26,27 the upregulation of stem cell markers, such as CXCR4, β1 integrin or Notch-1, [28][29][30][31][32] leading to the activation of alternative pathways circumventing HER2 signaling and the upregulation of pro-survival mediators, such as the inhibitor of apoptosis survivin. 33 Accordingly, it has been suggested that, although trastuzumab effectively targets cancer-initiating cells, a clinical resistance to trastuzumab may counter-intuitively be driven by breast CSCs.…”
Section: Epithelial-to-mesenchymal Transition (Emt) Confers Primary Rmentioning
confidence: 99%
“…Targeting of the integrins has reached clinical trials for the inhibition of angiogenesis (Avraamides et al 2008). Recent reports have also shown that blocking integrin functions can enhance the responsiveness of breast tumor cells to therapies, including radiation and Her-2 targeting (Lesniak et al 2009;Park et al 2008).…”
Section: How Targeting Cell -Matrix Interactions Will Improve Cancer mentioning
confidence: 99%